Detection of Barrett’s neoplasia with a near-infrared fluorescent heterodimeric peptide - Chen, Jing; Jiang, Yang; Chang, Tse-Shao; Rubenstein, Joel H.; Kwon, Richard S.; Wamsteker, Erik J.; Prabhu, Anoop; Zhao, Lili; Appelman, Henry D.; Owens, Scott R.; Beer, David G.; Turgeon, D. Kim; Seibel, Eric J.; Wang, Thomas D. (Endoscopy, 2022)
Background Esophageal adenocarcinoma (EAC) is a molecularly heterogeneous disease with poor prognosis that is rising rapidly in incidence. We aimed to demonstrate specific binding by a peptide heterodimer to Barrett’s neoplasia in human subjects.Methods Peptide monomers specific for EGFR and ErbB2 were arranged in a heterodimer configuration and labeled with IRDye800. This near-infrared (NIR) contrast agent was topically administered to patients with Barrett’s esophagus (BE) undergoing either endoscopic therapy or surveillance. Fluorescence images were collected using a flexible fiber accessory passed through the instrument channel of an upper gastrointestinal endoscope. Fluorescence images were collected from 31 BE patients. A deep learning model was used to segment the target (T) and background (B) regions.Results The mean target-to-background (T/B) ratio was significantly greater for high grade dysplasia (HGD) and EAC versus BE, low grade dysplasia (LGD), and squamous epithelium. At a T/B ratio of 1.5, sensitivity and specificity of 94.1 % and 92.6 %, respectively, were achieved for the detection of Barrett’s neoplasia with an area under the curve of 0.95. No adverse events attributed to the heterodimer were found. EGFR and ErbB2 expression were validated in the resected specimens.Conclusions This “first-in-human” clinical study demonstrates the feasibility of detection of early Barrett’s neoplasia using a NIR-labeled peptide heterodimer.